Photobiocatalytic Oxyfunctionalization with High Reaction Rate using a Baeyer-Villiger Monooxygenase from Burkholderia xenovorans in Metabolically Engineered Cyanobacteria - Erdem Elif; Malihan-Yap Lenny; Assil-Companioni Leen; Grimm Hanna; Barone Giovanni Davide; Serveau-Avesque Carole; Amouric Agnes; Duquesne Katia; de Berardinis Véronique; Allahverdiyeva Yagut; Alphand Véronique; Kourist Robert (AMER CHEMICAL SOC, 2022)
Baeyer-Villiger monooxygenases (BVMOs) catalyze the oxidation of ketones to lactones under very mild reaction conditions. This enzymatic route is hindered by the requirement of a stoichiometric supply of auxiliary substrates for cofactor recycling and difficulties with supplying the necessary oxygen. The recombinant production of BVMO in cyanobacteria allows the substitution of auxiliary organic cosubstrates with water as an electron donor and the utilization of oxygen generated by photosynthetic water splitting. Herein, we report the identification of a BVMO from Burkholderia xenovorans (BVMOXeno) that exhibits higher reaction rates in comparison to currently identified BVMOs. We report a 10-fold increase in specific activity in comparison to cyclohexanone monooxygenase (CHMOAcineto) in Synechocystis sp. PCC 6803 (25 vs 2.3 U g(DCW)(-1) at an optical density of OD750 = 10) and an initial rate of 3.7 +/- 0.2 mM h(-1). While the cells containing CHMOAcineto showed a considerable reduction of cyclohexanone to cyclohexanol, this unwanted side reaction was almost completely suppressed for BVMOXeno, which was attributed to the much faster lactone formation and a 10-fold lower KM value of BVMOXeno toward cyclohexanone. Furthermore, the whole-cell catalyst showed outstanding stereoselectivity. These results show that, despite the self-shading of the cells, high specific activities can be obtained at elevated cell densities and even further increased through manipulation of the photosynthetic electron transport chain (PETC). The obtained rates of up to 3.7 mM h-1 underline the usefulness of oxygenic cyanobacteria as a chassis for enzymatic oxidation reactions. The photosynthetic oxygen evolution can contribute to alleviating the highly problematic oxygen mass-transfer limitation of oxygendependent enzymatic processes.